Avaliação da bioatividade de peptídeos gerados por hidrólise enzimática da fração lectina de grãos de soja (Glycine max L. Merrill) - Lima, Anna Karoline de Sousa (2024)
The bioactivity of soybean lectin is widely reported in the literature, with these bioactivities generally attributed to specific sequences within the molecule, known as bioactive peptides, which exhibit superior performance compared to the parent protein due to their size and chemical characteristics. The primary method for producing these peptides is through enzymatic hydrolysis of the parent protein. There is a gap in the knowledge regarding the potential of peptides obtained by enzymatic hydrolysis of soybean lectin. Therefore, this research aimed to purify and hydrolyze soybean lectin, and to evaluate the physicochemical and bioactive characteristics of the generated peptides. The lectin was purified by precipitation (salting out), ion exchange chromatography, and size exclusion chromatography. The resulting lectin fraction was then hydrolyzed using the enzymes alcalase, papain, and a sequential alcalase-papain process. The generated peptides were characterized by mass spectrometry, FTIR, SEM, TGA, and Tris-Tricine gel electrophoresis. The stability of the peptides was assessed through in vitro digestion simulation, followed by analyses of intrinsic fluorescence, particle size, and zeta potential. The antioxidant potential of the peptides was evaluated by the in vitro scavenging percentage of ABTS and DPPH radicals, and the antiproliferative activity was assessed in human colon adenocarcinoma cells. In silico analyses were conducted to predict bioactivity, and the binding of peptides to molecules related to these bioactivities was evaluated through molecular docking. The purification resulted in a semi-purified lectin with the presence of a 31 kDa band and lower molecular weight bands. Hydrolysis produced three hydrolysates: HA (alcalase), HP (papain), and HAP (alcalase-papain), generating 393, 387, and 489 peptides in the experiments, respectively, with sizes ranging from 6-2500 Da. Due to a higher degree of hydrolysis and smaller peptides, as well as more bioactivity predictions, the HAP peptide was selected for physicochemical and bioactivity characterization. FTIR analysis showed that the HAP peptide is predominantly composed of β-sheet secondary structures, and TGA analysis demonstrated thermostability in both the lectin fraction and the HAP hydrolysate. Microscopy revealed that the peptides tend to form clumps with a porous surface, while the lectin fraction exhibits a flatter and thinner structure. After digestion, changes in the tertiary structure of the protein were observed, and the aggregation of hydrolysates was confirmed by particle size analysis. The antioxidant potential evaluation of the HAP peptide showed scavenging percentages of 49,34% and 68,69% for ABTS and DPPH radicals, respectively. The antiproliferative activity showed that both the lectin fraction and HAP reduced the viability of the HT-29 cell line, with IC50 values of 258,4 and 188,9 µg/mL for the lectin fraction and hydrolysate, respectively. For the LoVo cell line, the IC50 values were 193.2 and 175,6 µg/mL, and HAP induced cell apoptosis as demonstrated by flow cytometry. In silico analyses predicted the following bioactivities for HAP: antioxidant, ACE inhibition, DPP-IV inhibition, anti-inflammatory, anti-angiogenic, quorum sensing inhibition, and anticancer activity. The binding of different peptides to molecules related to these activities was also evaluated to understand the mechanism of action of the peptides.